2015
DOI: 10.1021/acs.macromol.5b00086
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene-g-poly(cyclohexene oxide) by Mechanistic Transformation from ROMP to Visible Light-Induced Free Radical Promoted Cationic Polymerization

Abstract: A novel polymerization mechanism transformation strategy, combining ring-opening metathesis polymerization (ROMP) and visible light induced cationic polymerization, is successfully applied for the synthesis of polyethylene-graf t-poly(cyclohexene oxide) (PE-g-PCHO). First, cis-cyclooctene (COE) was polymerized via ROMP in the presence of a chain transfer agent and quantitatively hydrobrominated to give bromo functional polyethylene (PEBr). Subsequent irradiation of PE-Br in the visible range using dimanganese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 72 publications
1
30
0
Order By: Relevance
“…As can be seen that the disappearances of characteristic alkyne and azide peaks; methine (c) 4.7 ppm and methylene (d) protons at 2.5 ppm of PCL-alkyne and methine (a) and methylene (b) as well as the appearance of triazole proton (c) at 8.12 ppm were great evidences for the successful formation of clicked product PP-g-PCL [54]. Also in Figure 5, the structure of another PPg-PEG copolymer was also analyzed by 1 H-NMR spectroscopy and the similar results were observed [45,[55][56][57][58]. Furthermore, the composition of graft copolymers were also calculated from integration ratios of specific resonances belonging to each segments by using following formulas Equations (1) and (2) for PP-g-PCL and PP-g-PEG and the result summarized in Table 1.…”
Section: Resultssupporting
confidence: 65%
“…As can be seen that the disappearances of characteristic alkyne and azide peaks; methine (c) 4.7 ppm and methylene (d) protons at 2.5 ppm of PCL-alkyne and methine (a) and methylene (b) as well as the appearance of triazole proton (c) at 8.12 ppm were great evidences for the successful formation of clicked product PP-g-PCL [54]. Also in Figure 5, the structure of another PPg-PEG copolymer was also analyzed by 1 H-NMR spectroscopy and the similar results were observed [45,[55][56][57][58]. Furthermore, the composition of graft copolymers were also calculated from integration ratios of specific resonances belonging to each segments by using following formulas Equations (1) and (2) for PP-g-PCL and PP-g-PEG and the result summarized in Table 1.…”
Section: Resultssupporting
confidence: 65%
“…We have recently shown that polyolefin modifications can be achieved by the use of a “grafting from” approach by taking advantage of the use of such functional groups bound to the side chain of polyolefins in course of a postsynthesis modification approach. This way, numerous polyolefin‐based graft copolymers have been synthesized by either conventional and controlled/living radical polymerizations or free radical promoted cationic polymerization …”
Section: Introductionmentioning
confidence: 99%
“…[19] Further studies in this line are in progress, together with optimization of the reaction conditions to achieve aliving/controlled (co-)polymerization, preferably by photochemical processes. Theresulting semicrystalline thermoplastic unsaturated polyacetals exhibited molar masses (M n app )o fu pt o3 6kgmol À1 with ad ispersity of around 1.4.…”
Section: Angewandte Chemiementioning
confidence: 99%